2007
DOI: 10.1634/stemcells.2007-0175
|View full text |Cite
|
Sign up to set email alerts
|

Extending Jak2V617F and MplW515 Mutation Analysis to Single Hematopoietic Colonies and B and T Lymphocytes

Abstract: JAK2V617F and MPLW515L/K are myeloproliferative disorder (MPD)-associated mutations. We genotyped 552 individual hematopoietic colonies obtained by CD34؉ cell culture from 16 affected patients (13 JAK2V617F and 3 MPLW515L/K) to determine (a) the proportion of colonies harboring a particular mutation in the presence or absence of cytokines, (b) the lineage distribution of endogenous colonies for each mutation, and (c) the differences (if any) in the pattern of mutation among the various MPDs, as established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 28 publications
(47 reference statements)
4
45
0
Order By: Relevance
“…Jamieson et al 21 have demonstrated that the mutation was present in flow cytometrypurified populations of hematopoietic stem cells, common myeloid progenitors, granulocyte/macrophage progenitors and megakaryocytic/erythroid progenitors. Similar findings in different hematopoietic cell lineages have been reported in PV and PMF patients [22][23][24][25][26] although lymphoid cells were involved in only a proportion of the patients; 27 furthermore, the occurrence of the mutation in a myelo-lymphoid progenitor in patients with PV and PMF has been demonstrated. 28 Mitotic recombination of the short arm of chromosome 9, resulting in homozygosity for the V617F allele at the single cell level, happens in about 30% of patients with PV and PMF as compared to only 2-4% of those with ET.…”
Section: And Vainchenker and Constantinescu 15supporting
confidence: 80%
“…Jamieson et al 21 have demonstrated that the mutation was present in flow cytometrypurified populations of hematopoietic stem cells, common myeloid progenitors, granulocyte/macrophage progenitors and megakaryocytic/erythroid progenitors. Similar findings in different hematopoietic cell lineages have been reported in PV and PMF patients [22][23][24][25][26] although lymphoid cells were involved in only a proportion of the patients; 27 furthermore, the occurrence of the mutation in a myelo-lymphoid progenitor in patients with PV and PMF has been demonstrated. 28 Mitotic recombination of the short arm of chromosome 9, resulting in homozygosity for the V617F allele at the single cell level, happens in about 30% of patients with PV and PMF as compared to only 2-4% of those with ET.…”
Section: And Vainchenker and Constantinescu 15supporting
confidence: 80%
“…However, we are intrigued by the possibility that a low JAK2V617F allele burden is a surrogate for the coexistence of a more dominant JAK2V617F-negative clone with a higher propensity to undergo clonal evolution. Such a contention is supported by increasing evidence that point to JAK2V617F as a secondary event in the clonal hierarchy of myeloproliferative neoplasms 27 and is consistent with the development of mutation-negative leukemic transformation in mutation-positive patients. 28 Also in support of the scenario for competing clones, we have previously shown the concurrent occurrence of JAK2V617F and MPLW515L/K in some patients with PMF 29 and clonal dominance by the latter in such an instance.…”
Section: Discussionmentioning
confidence: 77%
“…The present study examined two ET patients and found that the cell lineages involved with the JAK2-V617F mutation were different from those with the MPL-W515L mutation (3,4). Whether acquisition of the JAK2-V617F mutation is an early event or not in the pathogenesis of MPNs is one of the important issues to be resolved.…”
Section: Discussionmentioning
confidence: 77%
“…The mutations of the Janus Kinase 2 (JAK2) gene and thrombopoietin receptor (c-MPL) gene are detected in bcr/abl negative chronic myeloproliferative neoplasm (MPN), which primarily includes polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis with regard to the conclusions that can be drawn from these findings (3,4).…”
Section: Introductionmentioning
confidence: 99%